Komparasi Munculnya Liberalisme Ekonomi di Indonesia dan Burma - Hatib Abdul Kadir (Universitas Gadjah Mada, 2017)
This paper explores the genealogy of the birth of the economic growth system in Indonesia and Burma. First, it is a major transformation that occurs in both countries in the form of commodification of land, labor and money. And the formation of pluralism in the colonial society. Second, the transformation of capitalism in Burma that enters through the system of bureaucratic governance, education and social order in rural communities. Third, the study of comparative application of economic liberalism in Indonesia and Burma and its social effects. And the emergence of middle class society who came from outside of original community. The author uses Karl Polanyi’s approach for looking at the social effects of economic liberalism, based on the transformation of three things: the privatization of the land, the commodification of labor and the emergence of the system of money and debt. This comparison primarily uses extensive data from J.S Furnivall in view of the application of an economic liberalism system which is then enriched with studies from other economic historians, such as Thomas Lindblad, Anne Booth and the study of political economics, Richard Robison.